When Surfaces Matter: Personal Shopper as Posthuman Exploration of Subjectivity Through Media - Sticchi, Francesco (Scenari, 2021)
This essay addresses Personal Shopper as an essential case study to examine the radical transformation of subjectivity taking place through the relation with digital technology and screens in our everyday life. The discussion will be mainly directed on how the film describes the psychological and emotional conflict embodied by the main character, Maureen, as the result of a complex entanglement with spaces, technological, and material surfaces. The decentring of Maureen on the physical context surrounding her, reveals her identity as an ecological notion, an immanent and enworlded process of continuous remediation with the environment. Employing Giuliana Bruno’s work and Mikhail Bakhtin’s notion of the Chronotope, I will demonstrate how Personal Shopper, far from describing technological developments as the accomplishment of a humanist ideal, allows us to tackle, without conciliating answers, the radical crisis of the human characterising our age.